On the relations between the grammatical codifications of the serbian and ‘illyrian’ literary languages by Karadžić (1818) and Babukić (1836): plagiarism and adaptation - Silobrčić, Ivan (Vilnius University Open Series, 2024)
Contemporary debates regarding whether or not the Croatian literary language is equal to the Serbian literary language seldom touch upon the matter of the Illyrian national revival and its organiser, Ljudevit Gaj (German: Ludwig von Gay). Their Illyrian literary language, whose purpose was to become the common literary language of all Southern Slavs, was codified in Zagreb in the Osnova slovnice slavjanske narěčja ilirskoga by the Croatian linguist Vjekoslav Babukić, first published in the mouthpiece of the Illyrian movement Danica ilirska in 1836. This short grammatical sketch corresponds to Karadžić’s grammar in his dictionary Српски рјечник (1818) far more than it does not, and this fact is dealt with awkwardly in the histories of the Croatian language. In essence, the differences in Babukić’s text with respect to the source text consist in Slovene-Kajkavian lexemes and grammatemes, but they are not great in number. In this article, we propose to analyse the claim that Babukić’s short grammatical sketch constitutes a case of plagiarism and of adaptation with regard to the grammar appended to Karadžić’s dictionary, as seen through the scientific literature covering the Illyrian National Movement.